Comparison of properties of prefabricated interlocking pavement blocks cured at different conditions - Uygunoğlu, Tayfun (Revista de la Construcción. Journal of Construction, 2016)
In this study, influence of curing condition and fly ash content on properties of pre-fabricated concrete interlocking blocks (PCIBs) were investigated. The blocks were produced with crushed sand stone (fine) and crushed stone (coarse) as aggregate. Also, fly ash was added to mixtures in different ratio by replacing the cement from 0 to 30%. PCIBs were cured in three different types as steam cure, water-pool cure and wet cure. Compressive strength, tensile splitting strength, density, apparent porosity, water absorption by weight and abrasion resistance of PCIBs was determined. When comparing the PCIBs, the use of wet cure results in lower physical and mechanical properties after 28 days. By contrast, water- pool and steam cure gives better result on mechanical and physical properties. Also, replacement of cement with fly ash (from 10% to 20%) has a significant effect in increasing important properties of PCIBs.